Anti‑Diabetic Effect of Lactobacillus Paracasei Isolated from Malaysian Water Kefir Grains - Talib, Noorshafadzilah; Mohamad, Nurul Elyani; Yeap, Swee Keong; Ho, Chai Ling; Masarudin, Mas Jaffri; Abd-Aziz, Suraini; Izham, Mira Nadiah Mohd; Kumar, Muganti Rajah; Hussin, Yazmin; Alitheen, Noorjahan Banu (Springer Nature, 2023)
The prevalence of type 2 diabetes mellitus (T2DM) is alarming because it is always linked to the increase in chronic diseases, mortality, and socioeconomic burden. Water kefir has a wide range of functional and probiotic characteristics attributed to the microorganisms present in the kefir grains. The present study aims to evaluate the in vivo anti-diabetic potential of the isolated Lactobacillus paracasei from Malaysian water kefir grains (MWKG) which was reported to have excellent probiotic properties and high antioxidant activities as reported previously. High-fat diet/streptozotocin (HFD/STZ) induction was used to obtain a T2DM model followed by treatment with the isolated L. paracasei from MWKG. The levels of glucose, insulin, and in vivo liver antioxidants were quantified after 14 weeks. Gene expression analysis of the liver was also carried out using microarray analysis, and several genes were selected for validation using quantitative real-time PCR. Insulin tolerance test demonstrated that the L. paracasei isolated from the MWKG alleviated T2DM by improving the area under the curve of the insulin tolerance test whereby low-dose and high-dose concentrations treated groups showed 2424.50±437.02 mmol/L·min and 2017.50±347.09 mmol/L·min, respectively, compared to untreated diabetic mice which was 3884.50±39.36 mmol/ L·min. Additionally, treatment with the isolated L. paracasei from MWKG regulated the expression of several genes related to glucose homeostasis and lipid metabolism in diabetic mice. These results suggested that the isolated L. paracasei from MWKG could be a potential dietary supplement for T2DM.